Total Physical Response and Direct Method in Students’ Vocabulary Mastery Learning - Choiril Anwar; Diah Fitriani (SHAHIH: Journal of Islamicate Multidisciplinary, 2016)
AbstractThe objective of this study was to test which one of the two methods (TPR and DM) were more effective to improve the students’ vocabulary mastery. The population of this study was all of the fifth graders of SD Islam Sultan Agung 4 Semarang in the academic year of 2015/2016. The instrument of the study was vocabulary test consisted of multiple choice items and matching items. Before treatment was given, pre-test was conducted to both groups. Meanwhile, post-test was conducted after the treatment had finished. The result showed that the mean of the experimental and control group in pre-test were 64.35 and 65.30, respectively. After being given the treatment, post-test was conducted in both groups. The t-test calculation showed that there was a significant difference. So, Total Physical Response method was more effective than Direct Method in learning English Vocabulary to the fifth graders of Elementary Students. Keywords: Total Physical Response, Direct method, and Vocabulary AbstrakTujuan dari penelitian ini adalah untuk menguji mana dari dua metode (TPR dan DM) yang lebih efektif untuk meningkatkan kemampuan penguasaan kosa kata siswa.  Subjek penelitiannya adalah semua siswa kelas 5 SD Islam Sultan Agung 4 Semarang Tahun Ajaran 2015/2016. Instrumen penelitiannya berupa tes kosa kata yang terdiri dari pilihan ganda dan menjodohkan. Sebelum perlakuan diberikan, kedua grup diberikan pre-test. Sedangkan post-test diberikan setelah perlakuan selesai. Hasilnya menunjukkan bahwa rata-rata grup eksperimen dan kontrol berturut-turut adalah 64.35 dan 65.30. Setelah diberikan perlakuan, kedua grup diberikan post-test. Nilai rata-rata untuk kedua grup berturut-turut adalah 78.65 dan 71.70. Perhitungan t-test menunjukkan adanya perbedaan yang mencolok. Jadi, metode Total Physical Response lebih efektif daripada Direct Method dalam pembelajaran kosa kata Bahasa Inggris pada siswa kelas lima sekolah dasar. Kata Kunci:  Total Physical Response, Direct method, and Vocabulary